The complete mitochondrial genome of the Rana kukunoris (Anura: Ranidae) from Inner Mongolia, China - Jifei Wang; Zongzhi Li; Hui Gao; Zhensheng Liu; Liwei Teng (Mitochondrial DNA. Part B. Resources, 2020)
We determined the whole mtNDA genome of the Plateau brown frog (Rana kukunoris) in Helan Mountains, Inner Mongolia. The complete mitochondrial genome consists of 13 protein-coding, 22 tRNA, 2 rRNA genes, and 1 control region (CR), and its total length is 16,644 bp. Three overlaps among the 13 protein-coding genes were found: ATP8/ATP6, ND4L/ND4, and ND5/ND6. The CR is 837 bp in length. The nucleotide composition is 27.49% A, 29.06% T, 14.77% G, 28.68% C. The result of phylogenetic analysis showed that there was close genetic relationship between R. kukunoris and Rana chensinensis.